2002
DOI: 10.1097/00000374-200203000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Systemic Alcohol and Central Nicotine Administration into Ventral Tegmental Area on Dopamine Release in the Nucleus Accumbens

Abstract: These data support the hypothesis that the reinforcing effects of ethanol are at least partially mediated through the nicotinic receptors in the VTA. Furthermore, administration of selective nicotinic antagonists may be of therapeutic potential in reducing the rewarding effects of ethanol. The data also suggest that the combined effects of ethanol and nicotine on the "reward pathway" may be a contributing factor to the high incidence of smoking in alcoholics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 50 publications
6
75
0
1
Order By: Relevance
“…In contrast, the co-administration of nicotine and alcohol did not result in an additive effect on accumbal DA levels as has been reported previously [70,88]. The difference in the results could be attributed to the difference in the doses of alcohol and nicotine [88] as well as the experimental design where the rats were exposed to either alcohol or nicotine before the co-administration of both alcohol and nicotine [31].…”
Section: Effect Of Nt69l On Nicotine-and Alcohol-induced Biochemical supporting
confidence: 51%
See 2 more Smart Citations
“…In contrast, the co-administration of nicotine and alcohol did not result in an additive effect on accumbal DA levels as has been reported previously [70,88]. The difference in the results could be attributed to the difference in the doses of alcohol and nicotine [88] as well as the experimental design where the rats were exposed to either alcohol or nicotine before the co-administration of both alcohol and nicotine [31].…”
Section: Effect Of Nt69l On Nicotine-and Alcohol-induced Biochemical supporting
confidence: 51%
“…This part of the brain is strongly implicated in the reinforcing effects of drugs, including alcohol and nicotine [69] and receives heavy dopaminergic input from the ventral tegmental area (VTA). Together the NA and VTA comprise an important component of the mesolimbic 'reward pathway' [31,70]. Acute nicotine elevates dialysate DA levels in the NA [19,71,72].…”
Section: Effect Of Nt69l On Nicotine-and Alcohol-induced Biochemical mentioning
confidence: 99%
See 1 more Smart Citation
“…Corroborating this suggestion, it has been demonstrated that ethanol enhances agonist-induced ion flux through nicotinic receptors (Aistrup et al, 1999;Cardoso et al, 1999) and that ethanol-induced stimulation of mesolimbic dopamine systems involves the activation of nicotinic receptors (Soderpalm et al, 2000). Despite these findings, there have been relatively few animal studies of the basic neurobiology of the combined nicotine and ethanol exposure, and while some studies suggest that nicotine has a modulatory effect on ethanol effects through its cholinergic actions, others show no marked interactions and still others show augmented effects (Bachtell and Ryabinin, 2001;Penland et al, 2001;Tizabi et al, 2002Tizabi et al, , 2003. Accordingly, the role of cholinergic systems in the anxiety alterations associated with nicotine and ethanol adolescent exposure needs to be tested in subsequent studies.…”
Section: Neurobiology Of Nicotine Vs Ethanol Interactionsmentioning
confidence: 99%
“…Activation of nicotinic acetylcholine receptors (nAChRs) is a common event in the pathway used by several addictive drugs to stimulate the mesolimbic DA system, which is a relevant component of the brain stimulation reward pathway [3,4]. Thus, in rats systemic nicotine or alcohol administration elevates extracellular DA levels in the nucleus accumbens, an effect that requires stimulation of nAChRs in this area as well as in the ventral tegmental one, in which the mesolimbic dopaminergic cell bodies are located [5][6][7].…”
Section: Introductionmentioning
confidence: 99%